PENERAPAN TEKNIK ZERO WASTE PADA PEMBUATAN BUSANA DEMI COUTURE: Penerapan Metode Zero Waste pada Pembuatan Busana Demi Couture - Putri, Shella Wardhani (MODA, 2022)
The development of dynamic fashion trends greatly affects the fashion industry, where it has an impact on the increase in the amount of waste every year. Considering the increasing use of synthetic fabrics because they are considered more efficient, the waste reduction must also be carried out through efficient use of fabrics. So that it encourages designers to make changes in the design and production process so that the resulting product does not produce a lot of waste and does not even produce waste. Zero waste is a technique that can be used to reduce residual waste from production because the waste generated is less than 15%. The application of the zero waste method in Indonesia has been applied by several ready-to-wear fashion brands. Thus, the application of the zero-waste technique in this study was carried out on clothes for the sake of couture, because clothes for couture that use a lot of various design lines and silhouette shapes, make clothes for couture tend to produce more waste. This study using a qualitative method, through the collection of observational and exploratory data on a zero waste pattern. The use of this method is based on the purpose of the study, which is to show that zero waste can be the right solution in reducing fabric waste from clothing production for the sake of couture, so that the use of fabric is more optimal. Keywords : Fashion, Zero Waste, Demi couture.